Niagara County, New York: Its Role in the Patriot War - Aikin, Bruce (Ontario History)

(untitled) (The Ontario Historical Society, 2023)
This article addresses several topics related to Niagara County, New York: the steamboat Caroline and its destruction and how Americans responded; the secret Hunter’s Lodges and, more specifically, their support for the notorious rebel, Benjamin Lett; incidents connected to Navy Island; William Lyon Mackenzie’s son James; Alexander McLeod’s trial; and the legacy of the Patriot War.